2004
DOI: 10.1111/j.1439-0442.2004.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Economic Evaluation of Different Methods of Newcastle Disease Vaccine Administration

Abstract: Two types of locally produced live vaccines (HB1 and La Sota--lentogenic strains) and inactivated oil adjuvant (IOAV) vaccine were used to compare the efficiency of three vaccination techniques, namely drinking water, ocular and spray on broiler chicks. The ocular route of vaccination on 1-day-old chicks followed by a booster dose on the third week through the same route induced a significantly higher level of haemagglutination inhibition antibody titre (P < 0.0001). The highest mean antibody titre was log(2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 5 publications
1
22
1
Order By: Relevance
“…In addition, necropsy findings revealed that lesions were less severe in all vaccinated groups as compared with positive control group. Protection against clinical signs and mortality following infection with vNDV in vaccinated birds has also been reported by other researchers (Boven et al, 2008, Fentie et al, 2014, Kapczynski & King, 2005, Degefa et al, 2004.…”
Section: Comparative Evaluation Of the Protective Efficacy Of Differementioning
confidence: 64%
“…In addition, necropsy findings revealed that lesions were less severe in all vaccinated groups as compared with positive control group. Protection against clinical signs and mortality following infection with vNDV in vaccinated birds has also been reported by other researchers (Boven et al, 2008, Fentie et al, 2014, Kapczynski & King, 2005, Degefa et al, 2004.…”
Section: Comparative Evaluation Of the Protective Efficacy Of Differementioning
confidence: 64%
“…The possible reason for the M failure of the vaccination in Keren poultry farm could be due to inappropriate vaccine administration that can lead to lower immune response. Degefa et al (2004) have also shown mass vaccination through drinking water route protects only 60% of the vaccinated flock. Additionally Dortmans et al (2012) showed that inadequate application of NDV vaccines worldwide account for the current outbreaks and spreading of virulent NDV field stains.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used method of administration of ND vaccine, La Sota in adult birds is orally through drinking water. Studies comparing the intraocular and oral routes of administration of these vaccines favoured the intraocular route [9,10], but these were mostly in young chickens.…”
Section: Introductionmentioning
confidence: 99%